2019
DOI: 10.1161/hypertensionaha.119.12684
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Hypertensive Patients

Abstract: In patients with hypertension, but without established cardiovascular disease, predictive factors for sudden cardiac death (SCD) remain undefined. We followed for an average of 10.3 years a cohort of 3242 initially untreated hypertensive patients without evidence of coronary or cerebrovascular heart disease at entry. All patients underwent a complete clinical examination which included ECG and 24-hour ambulatory blood pressure monitoring. At entry, the mean age of patients was 50.0 years, 45% were women, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 70 publications
6
28
0
2
Order By: Relevance
“…Anti-arrhythmic effects of sacubitril/valsartan in SHR arrhythmia. 11 Therefore, our results matched a specific pathophysiology of SCD with the available therapies to improve outcomes in patients with hypertensive heart disease. The current SHR model, characterized by ventricular hypertrophy and diastolic dysfunction, is associated with increased fibrosis, collagen deposition, and risk of SCD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Anti-arrhythmic effects of sacubitril/valsartan in SHR arrhythmia. 11 Therefore, our results matched a specific pathophysiology of SCD with the available therapies to improve outcomes in patients with hypertensive heart disease. The current SHR model, characterized by ventricular hypertrophy and diastolic dysfunction, is associated with increased fibrosis, collagen deposition, and risk of SCD.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown that LCZ696 improves systolic function, electrophysiological benefits, and down‐regulation of sodium and potassium channel protein expression, which are important contributors to systolic dysfunction‐related ventricular arrhythmia 9,10 . On the other hand, the rate of sudden cardiac death (SCD) is 0.3 per 100 patient‐years in hypertensive patients without cardiovascular diease 11 . SCD even accounts for around 20% of deaths in hypertensive patients with diastolic dysfunction and HF, which is also associated with malignant ventricular arrhythmia 2,12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although being male was an associated risk factor for ECG-LVH, LVH was a greater risk factor for cardiac death among females than among males 27 . Strong evidence was observed that ECG-LVH was a risk predictor of cardiovascular events including coronary heart disease, stroke and sudden cardiac death 2 , 3 , 8 , 28 30 . When LVH continued to progress, the prevalence of patients with cardiovascular diseases and their complications were more likely to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH) is considered a cardiac condition secondary to both structural and functional adaptation of the heart leading to many life-threatening complications like myocardial ischemia, left ventricular (LV) dysfunction, heart failure and even sudden cardiac death [1][2][3][4] . Several studies reported that the potential risk…”
Section: Abbreviationsmentioning
confidence: 99%
“…A study followed for an average of 10.3 years a cohort of 3242 initially untreated patients with hypertension without evidence of coronary or cerebrovascular heart disease at entry. 20 During follow-up, SCD occurred in 33 patients at a rate of 0.10 per 100 patient-years (95% confidence interval [CI], 0.07-0.14). The rate of SCD was 0.07 and 0.30 per 100 patient-years, respectively, in the cohort of patients without and with ECG LVH ( P < .01).…”
Section: Sudden Cardiac Death In Hf With Near-normal/normal Lvefmentioning
confidence: 99%